2023
DOI: 10.1101/2023.03.22.533562
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Homozygous ALS-linked mutations in TARDBP/TDP-43 lead to hypoactivity and synaptic abnormalities in human iPSC-derived motor neurons

Abstract: Cytoplasmic mislocalization and aggregation of the RNA-binding protein TDP-43 is a pathological hallmark of the motor neuron (MN) disease amyotrophic lateral sclerosis (ALS). Furthermore, while mutations in the TARDBP gene (encoding TDP-43) have been associated with ALS, the pathogenic consequences of these mutations remain poorly understood. Using CRISPR/Cas9, we engineered two homozygous knock-in iPSC lines carrying mutations in TARDBP encoding TDP-43A382Tand TDP-43G348C, two common yet understudied ALS TDP-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 111 publications
(217 reference statements)
2
12
0
Order By: Relevance
“…Given that, to our knowledge, similar cross-linking experiments characterizing TDP-43-bound transcripts have not yet been performed in human spinal cord specimens or spinal MN cultures, additional RNA-protein interaction studies may be needed to reveal cell type-specific TDP-43 binding targets. In line with this idea, recent studies have shown that different cell environments modulate the RNA processing functions of TDP- 43 49,50.…”
Section: Resultsmentioning
confidence: 77%
See 4 more Smart Citations
“…Given that, to our knowledge, similar cross-linking experiments characterizing TDP-43-bound transcripts have not yet been performed in human spinal cord specimens or spinal MN cultures, additional RNA-protein interaction studies may be needed to reveal cell type-specific TDP-43 binding targets. In line with this idea, recent studies have shown that different cell environments modulate the RNA processing functions of TDP- 43 49,50.…”
Section: Resultsmentioning
confidence: 77%
“…We have recently reported the generation of two homozygous knock-in iPSC lines with mutations in TARDBP coding for TDP-43 A382T or TDP-43 G348C , two frequent ALS variants of TDP-43. 43 To characterize the transcriptomic profiles of MNs differentiated from those cells, we performed next-generation RNA sequencing (RNA-seq) on total RNA extracted from mutant and isogenic control iPSC-derived MN cultures at 4-weeks post-plating ( Figure 1A and Supplemental Table S1 ). Analysis of normalized counts confirmed the expression of the MN markers ISL1 , MNX1 (Hb9), CHAT , and SLC18A3 (VAChT) ( Supplemental Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations